Feminist Teaching, Feminist Research, Feminist Supervision: Feminist Praxis In Adult Education - Christine Jarvis; Miriam Zukas (Adult Education Research Conference, 1998)
Feminist teaching and research have both been the subject of analytical discussions within adult education. Feminist research supervision has received rather less attention. We focus on two main issues, the role of experience and the feminist analysis of power/knowledge dynamics, in order to highlight the similarities and differences between the three areas.